Trends, Problems, and Policies of The Elderly Population in East Java Indonesia - Ida Bagus, Wirawan; Mayastuti, Mayastuti; Kristyono, Jokhanan (Technium Social Sciences Journal, 2022)
This study’s purpose is to describe the increasing elderly population trend, which has resulted in several problems in the province of East Java, Indonesia. The problem is that the life expectancy of the Indonesian population has continued to increase over the last two decades until it reaches an average of 70.8 years. This condition has significantly affected the trend of increasing Indonesia’s elderly population from 5.3 million people to the group of countries with the most significant number of elderly in the world. Through qualitative methods and a case study approach, this study has succeeded in interviewing 9 elderly informants from three different strata in the city of Surabaya, East Java, namely 3 informants from retired BKKBN officials, 3 elderly non-officials (staff), and 3 informants. Elderly without a pension (old-age social security). The content analysis method was also used to complement and refine the results of this study. This study found that increasing the number of older adults has led to several problems. These findings, among others, concern: (1) an increase in the dependency ratio between unproductive and economically productive populations. (2) health problems of the elderly population due to decreased body resistance. (3) the absence of adequate social security for the majority of the elderly (4) The capacity of social institutions in East Java is only 660 older adults, while there are 3.5 million that have not been handled (5) changes in intergenerational relations and lack of attention from elderly family members, causing more older adults are living in neglect.